Role of the Educational Atmosphere on Self-Efficacy Among Dental Students - Farshad Fatemeh; Kheirkhah Masoomeh; Virtanen Jorma I.; Hessari Hossein (Kerman University of Medical Sciences, 2025)
Background: Learning is due to behavioral changes in knowledge, skills, and attitude.
Objectives: The current research assesses the state of the atmosphere, educational environment, and self-efficacy domains. It also assesses how the educational environment affects dental students' sense of self-efficacy.
Methods: All clinical undergraduate dental students (N=190) at Tehran University of Medical Science's School of Dentistry were the focus of a descriptive-analytical research conducted in 2018. The Dundee Ready Education Environment Measure (DREEM), the demographic surveys, and the validated Persian version of the Sherer Self-Efficacy Scale were all employed by the researchers. The DREEM assessed students' perceptions of learning (PoL), teaching (PoT), academic self-perception (ASP), atmosphere (PoA), and social self-perception (SSP) in addition to other key categories. Demographic factors and educational data (academic level, admittance quota, overall average grade, final semester grade, employment experience outside of dentistry school, and self-perceived effectiveness) were included in the demographic questionnaire. The factors from the demographic questionnaire were compared to the educational climate and self-efficacy using linear regression analysis. Additionally, the association between the educational environment and self-efficacy was assessed using Pearson's correlation (rho) coefficient.
Results: The majority of clinical dentistry students (87.3%) were single, female (52.6%), and lived in dorms. All DREEM domains and the overall educational environment, with the exception of the PoT domain (p-value=0.302), significantly correlated positively with students' self-efficacy (p-value < 0.05). Self-efficacy and the overall educational environment are highly associated (p=0.001, rho=0.311).
Conclusion: A good educational atmosphere may enhance dental students’ self-efficacy.